Only Joking? Gustavo Sainz and La princesa del Palacio de Hierro: Funniness, Identity and the Post-Boom - Philip Swanson (Studies in 20th & 21st Century Literature, 1995)
The Mexican Gustavo Sainz has been seen as one of the initiators of the Latin American Post-Boom, largely because of the humor, accessibility and interest in popular culture that characterize some of his work and are often said to characterize the Post-Boom in general. His 1974 novel La princesa del Palacio de Hierro (The Princess of the Iron Palace) is a representative case. However, the Post-Boom's incorporation of "popular" elements within a relatively sophisticated "new novel" framework is a highly problematic process. This can be seen, in this novel, in the broad relationship of the "funny" and the "serious." The protagonist appears to revel in her comic account of transgressive adventures while revealing her simultaneous socialization into the norms of family and gender that are seemingly transgressed. At the same time, her own "fun" narration (transgressive of frivolous) is problematized further by the commentary of an implied author, figured as an intellectual and, possibly, a male. The function of the novel's humor thus emerges as both to transgress and mark the transgression, creating an interplay between the desire to affirm identity and an awareness that all identity is a construction based on hierarchical models. It is this sense of the contingency of identity that perhaps underlies the shift in emphasis and textual character represented by the Post-Boom.
Keywords: Gustavo Sainz; Post-Boom; Mexican literature; humor; popular culture; La princesa del Palacio de Hierro; The Princess of the Iron Palace; identity; hierarchy